2018
DOI: 10.1111/febs.14606
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, eryptosis and anemia: a pivotal mechanistic nexus in systemic diseases

Abstract: The average lifespan of circulating erythrocytes usually exceeds hundred days. Prior to that, however, erythrocytes may be exposed to oxidative stress in the circulation which could cause injury and trigger their suicidal death or eryptosis. Oxidative stress activates Ca -permeable nonselective cation channels in the cell membrane, thus, stimulating Ca entry and subsequent cell membrane scrambling resulting in phosphatidylserine exposure and activation of Ca -sensitive K channels leading to K exit, hyperpolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 281 publications
(373 reference statements)
2
121
0
7
Order By: Relevance
“…Through its effects on the membrane of RBCs (i.e., lipid peroxidation and protein oxidation) and caspase 3 activation (93, 94), oxidative stress is a key modulator of RBC rheological properties. Moreover, oxidative stress is able to activate Ca 2+ -permeable non-selective cation channels in the RBC membrane, leading to the accumulation of Ca 2+ within RBCs, which can trigger RBC membrane scrambling, resulting in phosphatidylserine exposure and possibly in membrane bubbling and emission of MPs (95). In addition, the activation of Ca 2+ -sensitive K + channels can lead to K + exit, hyperpolarization, Cl − exit and cell shrinkage (95).…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through its effects on the membrane of RBCs (i.e., lipid peroxidation and protein oxidation) and caspase 3 activation (93, 94), oxidative stress is a key modulator of RBC rheological properties. Moreover, oxidative stress is able to activate Ca 2+ -permeable non-selective cation channels in the RBC membrane, leading to the accumulation of Ca 2+ within RBCs, which can trigger RBC membrane scrambling, resulting in phosphatidylserine exposure and possibly in membrane bubbling and emission of MPs (95). In addition, the activation of Ca 2+ -sensitive K + channels can lead to K + exit, hyperpolarization, Cl − exit and cell shrinkage (95).…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 99%
“…Moreover, oxidative stress is able to activate Ca 2+ -permeable non-selective cation channels in the RBC membrane, leading to the accumulation of Ca 2+ within RBCs, which can trigger RBC membrane scrambling, resulting in phosphatidylserine exposure and possibly in membrane bubbling and emission of MPs (95). In addition, the activation of Ca 2+ -sensitive K + channels can lead to K + exit, hyperpolarization, Cl − exit and cell shrinkage (95). Baskurt et al (96) demonstrated that superoxide anion caused a decrease in RBC deformability, a slight decrease in RBC aggregation and a large increase in RBC aggregates strength, meaning that the RBC aggregates formed are more robust upon oxidative stress.…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 99%
“…Недавнее исследование продемонстрировало, что анемия у пациентов с артритом должна, по крайней мере частично, вызывать усиленный эриптоз [58]. Увеличенный эриптоз сравним с усиленным окислительным стрессом и повышенным показателем внутриклеточных ионов Ca 2+ [56]. Заманчиво предположить, что увеличенное прилипание эриптозных эритроцитов к клеткам эндотелия сосудов может способствовать патофизиологии сосудистой окклюзии и ишемии у пациентов с артритом.…”
Section: эриптоз как элемент патогенеза анемииunclassified
“…Продолжительность жизни эритроцитов человека составляет от 100 до 120 дней. Старение эритроцитов -это естественный процесс, изучению которого посвящено много исследований, последние достижения в этой области отражены в ряде обзорных работ [1,56,179,241].…”
Section: Introductionunclassified
“…In addition, the therapeutic effects of erythropoietin are often limited due to iron deficiency in the hemodialysis patients (12). Given the high impact of oxidative stress on accelerating blood cell destruction and exacerbating anemia, especially in chronic conditions, new therapeutic approaches have been directed toward the use of antioxidants as potential agents in the improvement of anemia (13).…”
Section: Introductionmentioning
confidence: 99%